Full expensing and the corporation tax base - Stuart Adam; Helen Miller (Institute for Fiscal Studies (IFS), 2023)
This report discusses the temporary full-expensing policy and whether it should be made a permanent part of the corporate tax base.
Keywords: 330; Business and investment; Savings; pensions and wealth; Taxes and benefits; IFS Green Budget 2023; Corporate taxes; Firms; Investment; Tax; Productivity